IDENTIFIKASI POLA ALIRAN DI SEKITAR DAERAH GENANGAN BANJIR - Indra Satria; Azmeri Azmeri; Yulia Hayati (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
Johan Pahlawan Sub-district especially Leuhan Village and Blang Beurandang Village is a residential area that was hit by a flood inundation. Rainfall intensity and flow pattern conditions cause inundation. Puddles result in physical damage to home components and cause a number of losses, with varying levels of inundation and water levels. This analysis study was conducted with the aim of identifying the condition of the pattern of drainage flow around the flood inundation area. The research approach is in the form of quantitative and qualitative research. Identification results obtained: The pattern of land flow and drainage in the form of flow direction is in accordance with the topographic conditions of the study area, with channel conditions such as shrubs, constriction and at certain points with conditions of low contoured areas so that inundation is prone to improvements such as maintenance activities and repair.